Terahertz spectroscopy of charge transport in films of pristine and doped single-wall carbon nanotubes. (January 2018) - Gorshunov, B.P.; Zhukova, E.S.; Starovatykh, Ju.S.; Belyanchikov, M.A.; Grebenko, A.K.; Bubis, A.V.; Tsebro, V.I.; Tonkikh, A.A.; Rybkovskiy, D.V.; Nasibulin, A.G.; Kauppinen, E.I.; Obraztsova, E.D.
Abstract: Electrical transport mechanisms of 2D carbon nanotube networks are presently under intensive studies. The related experimental data are ambiguous and controversial. We report on terahertz-infrared spectra of optical conductivity and dielectric permittivity of thin transparent films composed of pristine and CuCl- or iodine-doped single-walled carbon nanotubes (SWCNTs) measured in the frequency range from 7 to 25 000 cm −1 and at temperatures from 5 to 300 K. Controversially to the existing results, we have not observed a clear signature of the so-called terahertz conductivity peak. Instead, a typical metallic-like frequency- and temperature-dependent behavior of the conductivity and permittivity has been discovered. It was attributed to the high quality interconnected SWCNT network providing the almost free pathways for charge carriers. Applying Drude conductivity model, we have determined the temperature and doping dependences of effective parameters of the carriers in the films: plasma frequency, scattering rate, mobility, mean-free path. The obtained results demonstrate a great potential of the material in the field of electromagnetic applications at frequencies up to few terahertz. Graphical abstract: Image 1